SPORTIZATION OF PHYSICAL EDUCATION PROCESS: ORIGINS AND ESSENCE (EDUCATION IN THE 21ST CENTURY, 2023)
This work discusses the need for sportization of physical education process in secondary school. There are some reasons for this – deterioration of schoolchildren’s health and motor preparedness, reduction in effectiveness of physical education classes and the role of physical education in secondary school.The current situation necessitates the introduction of new technologies and methodological approaches, which can promote modernization of physical education for schoolchildren of different age and gender.One of the innovation directions is the so-called sportization of the physical education in school.The analysis of methodical literature on this issue testifies that the ideas and principles of sportization were implemented in school programs for physical education already in 1930s. Scientifically based attempts at sportization of physical education process were made 50 years later in a number of Lithuanian schools.Later, in order to improve the efficiency of school physical education, high sports technologies were adapted, confirming the possibility of using sports for education and socialization of secondary school pupils.A new concept of “sports education” appeared in science, the elements and principles of sports training were introduced and there was a gradual reorientation of physical education in school for sport.The authors have analyzed the work in this direction carried out in different countries. Referring to the data of their own research, they believe that sectional forms of organization of physical culture and sports activities should complement the lessons aimed at education. Such lessons have a training effect and improve the functionality of schoolchildren’s organism.
Keywords: Physical culture, extracurricular activities, schoolchildren, sectional exercises, physical condition.